Modelling and Simulations of Dynamics of the Low-Floor Tramcar with Independently Rotating Wheels - Andrzej Chudz; Magdalena Sowinska (Communications - Scientific letters of the University of Zilina, 2015)
The article is devoted to the analysis of numerical simulation results of the tramcar dynamics. It presents the mathematical model of the one section of the low-floor tram with the bogie with independently rotating wheels. The simulations were performed according to different scenarios, connected with the track geometry, which seem to be dangerous for the tram behaviour e.g.: curving, gauge narrowing, track buckling, etc. Special attention was paid to wheel lateral displacement and forces occurring in wheel-rail contact. The simulation results reveal characteristic features of such an unconventional system of the tram, which can often demonstrate dynamics considered worse than in the conventional case of the tramcar.